2021
DOI: 10.1108/lht-05-2021-0157
|View full text |Cite
|
Sign up to set email alerts
|

Information Literacy Skills among Library and Information Science Professionals: a forecaster of Research Support Services

Abstract: PurposeThe present research aims to gauge the Information Literacy Skills (ILSs) of the University Library and Information Science Professionals (LISPs) of Pakistan and consider it as a forecaster of improved Research Support Services (RSSs).Design/methodology/approachThe purposive sampling method through a questionnaire was applied and administered (online and offline) to assemble data from LISPs of 219 universities of Pakistan. The questionnaire covered the eight factors of ILSs and four of RSSs.FindingsThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Information literacy of library and information science professionals Information literacy is an essential skill for modern life, and it is an essential professional skill for library and information systems science researchers and practitioners (Li et al, 2021;Tse et al, 2022). Ali and Ahmed (2022) investigated the information literacy skills of Pakistan's university library and information science professionals. They used regression to show that information literacy skill is a prerequisite for improving library and information science professionals' research support services.…”
Section: Transformation Of Librariesmentioning
confidence: 99%
“…Information literacy of library and information science professionals Information literacy is an essential skill for modern life, and it is an essential professional skill for library and information systems science researchers and practitioners (Li et al, 2021;Tse et al, 2022). Ali and Ahmed (2022) investigated the information literacy skills of Pakistan's university library and information science professionals. They used regression to show that information literacy skill is a prerequisite for improving library and information science professionals' research support services.…”
Section: Transformation Of Librariesmentioning
confidence: 99%
“…Their results showed that the high-performance group performs better than the low-performance group in six indicators, and information-based teaching and behavioral research data can best reflect the level of information literacy. Readers may also be interested in reading further into information literacy issues for information professionals (Ali and Ahmed, 2022), students (Soroya et al ., 2021), and related curricula (Batool et al ., 2022; Li and Chiu, 2022; Yew et al ., 2022).…”
Section: Advances In Learning Technologiesmentioning
confidence: 99%
“…They suggested that iSchools may explore the possibility of organizing more conferences and forums to exchange ideas on archival studies and education issues, which can attract more members worldwide and cooperate with other accreditation organizations of archival education. Readers may also be interested in a recent review of the curricula in programs related to library science (Yew et al , 2022) and information literacy skills among library and information science professionals (Ali and Ahmed, 2021).…”
Section: Ischool Archival Education and Contemporary Technologiesmentioning
confidence: 99%